Chickpea Plant Results Due to Liquid Organic Fertilizer Waste from Leaf Vegetable Waste and Tofu Liquid Waste - Lena Walunguru; Marsema Kaka Mone (The University of Lampung, 2025)
The use of organic fertilisers represents an effective and sustainable approach to enhancing soil quality. Purpose of this study is to determine the influence of several concentrations of liquid organic fertilizer (LOF) made from leaf vegetable waste and liquid waste and to find out the concentration that has the best effect on chickpea yield. The experiment used a randomized group design (GRD), consisting of 11 treatments, repeated three times. The treatment tested was the concentration of LOF from leaf vegetable waste and tofu liquid waste, namely 0, 25, 50, 75, 100, 125, 150, 175, 200, 225, and 250 ml/l. The data were analyzed with ANOVA, if significant, a further test is carried out with an Honest Significant Difference (HSD) 5%. Observation variables were 1) Plant growth, namely height of plant, leaves amount, diameter of stem, and branches amount, and 2) Plant yield, namely the pods amount, length of pod, weight each of pod, and pod weight each plant. Results of the study that concentration of 250 ml/l had a better effect on amount of pods (56.75 pods), pod length (19.29 cm), weight each pod (10.62 g), and pod weight each chickpea plant (602.17 g). Keywords: Concentration, Leaf vegetable waste, Liquid organic fertilizer, Growth and yield of chickpea, Tofu liquid waste